A/C magnetic hyperthermia of melanoma mediated by iron(0)/iron oxide core/shell magnetic nanoparticles : a mouse study - Balivada, Sivasai (Kansas State University, 2009)
There is renewed interest in magnetic hyperthermia as a treatment modality for cancer, especially when it is combined with other more traditional therapeutic approaches, such as the co-delivery of anticancer drugs or photodynamic therapy. The influence of bimagnetic nanoparticles (MNPs) combined with short external alternating magnetic field (AMF) exposure on the growth of subcutaneous mouse melanomas (B16-F10) was evaluated. Bimagnetic Fe/Fe3O4 core/shell nanoparticles were designed for cancer targeting after intratumoral or intravenous administration. Their inorganic center was protected against rapid biocorrosion by organic dopamine-oligoethylene glycol ligands. TCPP (4-tetracarboxyphenyl porphyrin) units were attached to the dopamine-oligoethylene glycol ligands. The magnetic hyperthermia results obtained after intratumoral injection indicated that micromolar concentrations of iron given within the modified core-shell Fe/Fe3O4 nanoparticles caused a significant anti-tumor effect on murine B16-F10 melanoma with three short 10-minute AMF exposures. There is a decrease in tumor size after intravenous administration of the MNPs followed by three consecutive days of AMF exposure. These results indicate that intratumoral administration of surface-modified MNPs can attenuate mouse melanoma after AMF exposure. Moreover, intravenous administration of these MNPs followed by AMF exposure attenuates melanomas, indicating that adequate amounts of TCPP-labeled stealth Fe/Fe3O4 nanoparticles can accumulate in murine melanoma after systemic delivery to allow effective magnetic hyperthermic therapy in a rodent tumor mode.
AC magnetic hyperthermia of melanoma mediated by iron(0)/iron oxide core/shell magnetic nanoparticles
Keywords: Magnetic hyperthermia; Melanoma; cancer; Magnetic nanoparticles; Health Sciences, Medicine and Surgery (0564); Health Sciences, Oncology (0992)